2018
DOI: 10.1097/rlu.0000000000002319
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Esophageal Squamous Cell Carcinoma Staged With 18F-FDG PET/CT

Abstract: A 15-year-old boy with autism and swallowing dysfunction presented with a 6-month history of fatigue, intermittent abdominal pain, and weight loss. He later became febrile and had multiple episodes of coffee ground emesis and melena stools. An upper endoscopy showed an esophageal mass, and a subsequent 18F-FDG PET/CT scan confirmed this finding. PET/CT also revealed metastatic disease in local lymph nodes, thus upstaging the patient and indicating poor prognosis. Consideration of these severe results and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Dawsey et al 27 found 145 cases ≤30 years of age in the literature published between 1925 and 2007. We could find only 40 cases of esophageal carcinoma diagnosed under 18 years of age in the literature 5–24,28–37 (Table 2). This included 29 males and 11 females, with a M/F ratio of 2.6/1.…”
Section: Discussionmentioning
confidence: 99%
“…Dawsey et al 27 found 145 cases ≤30 years of age in the literature published between 1925 and 2007. We could find only 40 cases of esophageal carcinoma diagnosed under 18 years of age in the literature 5–24,28–37 (Table 2). This included 29 males and 11 females, with a M/F ratio of 2.6/1.…”
Section: Discussionmentioning
confidence: 99%